Annual Plan 2011-12 Volume - I (General) Government of Andhra Pradesh - Planning Commission (Planning Commission, 2011)
Andhra Pradesh is endowed with abundant natural and human resources amid competitive socio-economic advantages. the state has a geographical area of 275.04 lakh hectares accounting for 8.37% of the Country's area constituting the 4th largest State in the country. With a projected population of 8.47 Crores as on 1st March, 2011, the state accounts for 7.16% of country's population making it the 5th most populous State. the State, situated in a tropical region and has the 974 km long coastline and stands as the 2nd longest in the country having rich potential for marine fisheries.
Planning Department, Government of Andhra Pradesh